Ketogenic diet with aerobic exercise can induce fat browning: potential roles of β-hydroxybutyrate - Kim, Sujin; Park, Dong-Ho; Moon, Sohee; Gu, Bonsang; Mantik, Keren Esther Kristina; Kwak, Hyo-Bum; Ryu, Ji-Kan; Kang, Ju-Hee (Frontiers in Nutrition, 2024)
Introduction Despite evidence suggesting that metabolic intermediates like β-HB influence white adipose tissue (WAT) metabolism, the precise molecular mechanisms remain unclear. The aim of this study was to investigate the impact of beta-hydroxybutyrate (β-HB) on the fat browning program and to explore the underlying molecular mechanisms using both in vitro and in vivo models. We assessed the effects of β-HB on fat browning in adipocytes using 3T3-L1 cells and rat models. Methods We evaluated the effects of β-HB on fat browning, thermogenesis, lipid accumulation, adipokine expression, and mitochondrial biogenesis by treating mature 3T3-L1 adipocytes with sodium β-HB for 24 h or by continuously exposing preadipocytes to β-HB during the 8-day differentiation process. Male Sprague Dawley rats were divided into control, exercise only (EX), ketogenic diet only (KD), and combined exercise and ketogenic diet (KE) groups for an 8-week intervention involving diet and/or exercise. After intervention, we evaluated WAT histology, plasma lipids and adipokines, and the expression of markers related to fat browning, thermogenesis and mitochondrial biogenesis in WAT of rats. Results In our adipocyte culture experiments, β-HB reduced intracellular lipid accumulation by enhancing lipolysis and stimulated the expression of thermogenic and fat browning genes like uncoupling protein 1 (UCP1), PR domain containing 16 (PRDM16), and adipokines such as fibroblast growth factor 21 (FGF21) and Fibronectin type III domain-containing protein 5 (FDNC5). Additionally, β-HB activated the AMPK-SIRT1-PGC-1α pathway, with UCP1 and PRDM16 upregulation mediated by β-HB intracellular action and SIRT1 activity. In animal experiments, KE group raised β-HB levels, decreasing body weight and blood lipids. KD with EX promoted WAT browning possibly via AMPK-SIRT1-PGC-1α, augmenting PRDM16, UCP1, FGF21, and FNDC5 expression. Conclusion β-HB induction via KD and/or EX shows potential in promoting WAT browning by activating mitochondrial biogenesis, lipolysis, and thermogenesis, suggesting that dietary and physical intervention inducing β-HB may benefit metabolic health.